Common and exceptional clinical features of molluscum contagiosum. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
When consisting of a single, non typical element, molluscum contagiosum can be hardly differentiated from other lesions. Dermoscopy shows a lobulated lesion with interlobular telangiectases. However, the histologic examination is diriment. Inflamed molluscum contagiosum should be sometimes differentiated from summer lichenoid dermatitis of the elbows.